Teacher Competence and Creativity in Developing Mathematics Learning Plans in Inclusive Schools - Sumandya, I Wayan; I Wayan Widana; I Putu Pasek Suryawan; I Nyoman Bagus Suweta Nugraha; Ni Wayan Widi Astuti (Universitas Pendidikan Ganesha, 2025)
Teachers' ability to develop effective lesson planning is a key factor in the success of learning. This study aims to analyze teachers' competence and creativity in developing inclusive mathematics lesson plans. The research uses a quantitative approach with an explanatory method. The sampling technique employed is purposive sampling, with a total of 600 selected teacher participants. The instrument used in this study is a questionnaire. The analysis procedure is conducted in two stages: the Measurement Model and the Structural Model. The analysis results show a path coefficient of 0.474 and a p-value of 0.006 (less than 0.05) between teacher competence and the development of mathematics lesson planning, indicating that teacher competence has a significant influence on the ability to design mathematics instruction that meets the needs of students in inclusive schools. Meanwhile, the path coefficient between teacher creativity and the development of mathematics lesson planning is 0.305, with a p-value of 0.04 (less than 0.05), indicating that teacher creativity significantly affects the ability to develop mathematics lesson plans in inclusive schools. The conclusion of the study highlights that improving teachers' competence and creativity in inclusive education requires collaboration between teachers, policymakers, and educational institutions. With this competence and creativity, teachers can face the challenges of inclusive learning, ensure all students have meaningful learning experiences, and optimally develop their potential.